Pengaruh Keputusan Investasi, Keputusan Pendanaan, Dan Kebijakan Deviden Terhadap Nilai Perusahaan Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia (BEI) Periode 2016-2020 - Ezizwita, Ezizwita; Nurazizah, Ratna (Jurnal Ekonomika Dan Bisnis (JEBS), 2021)
This study aims to prove and analyze the effect of investment decisions, funding decisions and dividend policies on firm value in manufacturing companies on the Indonesia Stock Exchange for the period 2016 to 2020. This study uses data from several manufacturing companies selected using the purposive sampling method. The data used is secondary data obtained through the information contained in the annual financial statements of the sample companies which can be accessed and downloaded through www.idx.go.id. The data used is from 2016 to 2020. The data analysis method is carried out using panel data regression analysis while hypothesis testing is carried out by t-statistical test and F-statistical test. The stages of data processing are carried out with the help of SPSS version 25. In accordance with the results of testing the first hypothesis, it is found that investment decisions have a positive effect on firm value in manufacturing companies on the Indonesia Stock Exchange. will further increase firm value, while other results find funding decisions and dividend policy have no significant effect on firm value. The findings obtained show that changes in firm value are not only influenced by funding decisions and dividend policies but are also influenced by other variables such as the company's liquidity position, company size or factors originating from outside the company.